Mammoth phylogeography south of the ice: large-scale sequencing of degraded DNA from temperate deposits - Enk, Jacob M. (My University, 2014)
Mammoths (Mammuthus) have been studied extensively at the genetic level. However due to both taphonomic and technological limitations, only one of several late Pleistocene mammoth species, the woolly mammoth (M. primigenius), has been investigated. This limits our impression of mammoth population history to the the northern latitudes, just one of several environments in which mammoths lived and went extinct. It also obscures their evolutionary chronology, which prevents proper climatic and biogeographic contextualization of their history. Fortunately recent technological advances in high-throughput sequencing and targeted enrichment promise to expand Pleistocene faunal population phylogeography to non-permafrost, non-cave burial contexts. However the capacity and behavior of these combined technologies for characterizing ancient DNA is largely unexplored, preventing efficient and routine use for population-level studies. In this thesis I test and apply these technologies to remains of mammoth species from throughout North America. I first demonstrate their potential for poorly-preserved DNA, and then I evaluate their efficient application to large sample sets, as well as for capturing complete nuclear genomes. I then use these technologies to sequence dozens of mitochondrial genomes from Columbian (M. columbi) and other non-woolly mammoths, reconstructing their matrilineal phylogeography south of the ice. The revealed patterns not only imply a deep chronology for mammoth matrilineal diversity, but also that North American mammoth evolution was occurred via separate episodes of interbreeding between resident and invading populations, and between ecotypes. Overall the biological and methodological discoveries afforded by this body of work outline future research avenues on mammoth evolution, behavior, and extinction.
Keywords: Mammoths; ancient DNA; high-throughput sequencing; targeted enrichment; Biological and Physical Anthropology; Biology; Biological and Physical Anthropology